Reveal The Growth Pattern and Condition Factors of Blue Swimming Crabs (Portunus pelagicus) in Estuary Ecosystem of Berombang, Labuhanbatu Regency, North Sumatera - Rivo Hasper Dimenta; Nurjannah Nurjannah (BIOEDUKASI, 2023)
The Blue swimming crab Portunus pelagicus which comes from subphylum Crustacea, specifically the Portunidae family, is one of the potential crabs that have high economic value in Labuhanbatu regency. This study aimed to reveal information on condition factors and the population growth pattern of P. pelagicus in the ecosystem of the Berombang river estuary. This study was conducted from November 2021 to January 2022, using the purposive random sample method in determining the sampling points. In collecting the samples of P. pelagicus, the researchers used fish traps called bubu with fresh fish as bait. Results showed that the growth pattern of P. pelagicus was negatively allometric, in which values ​​for males and females were 1.1552 and 2.2727, respectively. Furthermore, the results of the correlation analysis between the physical-chemical of waters to abundance of P. pelagicus indicated that positive correlation for water temperature (0.835), dissolved oxygen (DO) (0.778), and salinity (0.726) had an effect on the presence of P. pelagicus.